1998
DOI: 10.1073/pnas.95.1.270
|View full text |Cite
|
Sign up to set email alerts
|

Human cytolytic and interferon γ-secreting CD8+T lymphocytes specific forMycobacterium tuberculosis

Abstract: Protective immunity to Mycobacterium tuberculosis is poorly understood, but mounting evidence, at least in animal models, implicates major histocompatibility complex class I-restricted CD8 ؉ T cells as an essential component. By using a highly sensitive assay for single cell interferon ␥ release, we screened an array of M. tuberculosis antigenderived peptides congruent with HLA class I allele-specific motifs. We identified CD8؉ T cells specific for epitopes in the early secretory antigenic target 6 during acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
230
0
4

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 341 publications
(241 citation statements)
references
References 27 publications
7
230
0
4
Order By: Relevance
“…Briefly, cells were permeabilized with permeabilization buffer (BD PharMingen) for 30 min on ice, then washed with cell wash buffer (BD PharMingen) and incubated with anti-granulysin mAb, DH4 (18), antiperforin mAb, ␦G9 (Kamiya Biomedical, Seattle, WA) or isotype control mouse IgG1 (BD PharMingen), for 30 min, and then washed three times with cell wash buffer. The cells were then incubated with FITC goat F(abЈ) 2 anti-mouse IgG (Southern Biotechnology Associates, Birmingham, AL) for 30 min on ice. To detect Fas ligand (FasL; CD95), CD8 ϩ T cells were incubated with biotin-labeled anti-CD95 mAb, then with streptavidin-PE (both from BD PharMingen).…”
Section: Immunolabeling To Detect Ctl Effector Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, cells were permeabilized with permeabilization buffer (BD PharMingen) for 30 min on ice, then washed with cell wash buffer (BD PharMingen) and incubated with anti-granulysin mAb, DH4 (18), antiperforin mAb, ␦G9 (Kamiya Biomedical, Seattle, WA) or isotype control mouse IgG1 (BD PharMingen), for 30 min, and then washed three times with cell wash buffer. The cells were then incubated with FITC goat F(abЈ) 2 anti-mouse IgG (Southern Biotechnology Associates, Birmingham, AL) for 30 min on ice. To detect Fas ligand (FasL; CD95), CD8 ϩ T cells were incubated with biotin-labeled anti-CD95 mAb, then with streptavidin-PE (both from BD PharMingen).…”
Section: Immunolabeling To Detect Ctl Effector Moleculesmentioning
confidence: 99%
“…In humans infected with M. tuberculosis, CD8 ϩ T cells produce IFN-␥ in response to mycobacterial Ag, lyse M. tuberculosisinfected target cells (2,3), and can directly kill mycobacteria by secreting granulysin (4,5). Effective immunity against tuberculosis is likely to depend in part on priming and maintenance of Agspecific CD8 ϩ T cells.…”
mentioning
confidence: 99%
“…Evidence obtained from analysis of TAP-and CD1d-deficient mice as well as an earlier study of mice lacking the expression of ␤ 2 -microglobulin unequivocally demonstrated a significant contribution of MHC class I-restricted CD8 ϩ CTLs in clearing mycobacterial infection in mice (3,4). In humans, the potential role of CD8 ϩ T cells in protection against mycobacterial infection has been appreciated partially by isolating and characterizing mycobacteria-specific, MHC class I-restricted CD8 ϩ T cell lines (5). These studies focused on macrophages, the well-known reservoir for mycobacteria, as CTL target cells, that were either infected with mycobacteria or pulsed with mycobacteria-derived peptide Ags.…”
mentioning
confidence: 99%
“…It has been demonstrated that CD 8 + T-lymphocytes have cytolytic activity against the tuberculosis bacillus [12], and their deficiency can result in susceptibility to infection by M. tuberculosis [13]. However, the exact function of these cells in host defense remains controversial.…”
Section: Discussionmentioning
confidence: 99%